2009
DOI: 10.1111/j.1360-0443.2009.02710.x
|View full text |Cite
|
Sign up to set email alerts
|

Online support for smoking cessation: a systematic review of the literature

Abstract: Aim To examine the efficacy and acceptability of online, interactive interventions for smoking cessation and to identify treatment effect moderators and mediators. Methods A systematic review and meta-analysis of the literature (1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008) was conducted, finding 11 relevant randomized controlled trials. Data were extracted and risk ratios and risk differences estimated with a random effects model. Results The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
239
3
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 254 publications
(251 citation statements)
references
References 59 publications
(148 reference statements)
7
239
3
2
Order By: Relevance
“…In that case, results might be biased by the use of an intention to treat analysis that assumes those lost to follow-up are smoking. However, trials of internet-based smoking cessations interventions have actually shown that control conditions involving less engagement do not typically result in lower follow-up rates (Shahab & McEwen, 2009). Furthermore, the current trial will use evidence-based follow-up methods that resulted in similarly low attrition between two conditions in spite of a considerable difference in treatment intensity and engagement (Edwards, et al, 2002;Free, et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In that case, results might be biased by the use of an intention to treat analysis that assumes those lost to follow-up are smoking. However, trials of internet-based smoking cessations interventions have actually shown that control conditions involving less engagement do not typically result in lower follow-up rates (Shahab & McEwen, 2009). Furthermore, the current trial will use evidence-based follow-up methods that resulted in similarly low attrition between two conditions in spite of a considerable difference in treatment intensity and engagement (Edwards, et al, 2002;Free, et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…As recommended by the Russell Standard, this potential bias will be addressed by using an intention to treat analysis, in which smokers lost to follow-up will be counted as continuing smokers. Of the studies included in a recent meta-analysis of internetbased smoking cessation interventions the rate of loss to follow-up varied substantially; the range was 6% to 61% at approximately 6-months following enrolment (Shahab & McEwen, 2009). Since the present study uses evidence-based methods for enhancing response rates, it is assumed that the figure will be toward the lower end of this range and estimated to be no more than 20%.…”
Section: Recruitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Web-based interventions were used for improving specific behaviors such as smoking [15], alcohol consumption [16], sexual behavior [17], physical activity [18], and dietary behavior [19]. There have been relatively few studies using a Web-based intervention to promote cancer screenings.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the effectiveness of Internet smoking cessation programs was tested primarily in smokers with an intention to quit smoking and in younger samples of smokers in the age range of 20-40 years (Shahab & McEwen, 2009). However, in recent years, Internet use has particularly increased in older people.…”
Section: Introductionmentioning
confidence: 99%